Cross-Cultural Adaptation and Psychometric Evaluation of the Perceived Ability to Cope With Trauma Scale in Portuguese Patients With Breast Cancer - Lemos, Raquel (2022)
Funding: RL was supported by the 2018 Scientific Employment Stimulus from Fundação para a Ciência e Tecnologia, Portugal (CEECIND/04157/2018). DF, BS, and AO-M were supported by the BOUNCE project (grant agreement no. 777167), and AO-M was supported by the FAITH project (grant agreement no. 875358), both funded by the European Union’s Horizon 2020 Research and Innovation Programme.